Features of using social networks in self-learning foreign languages - O. Shumskyi (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The 21st century witnesses a significant surge in the role of a specific communication environment within a special network community. This phenomenon has catalysed the emergence of a new paradigm in educational activity, particularly in the realm of foreign languages. This paradigm, characterized by network learning and self-learning, is founded upon the principles of mass cooperation, the ideology of educational resource openness, and the networked organization of participants’ interaction. This article explores the possibilities and peculiarities of utilizing network technologies in students’ self-directed foreign language learning. Through network interaction, students can vastly expand the scope of linguistic self-education by leveraging social network cooperation, polymodal interaction, and the creation of virtual foreign language communicative environments. Central to this discussion are the main characteristics of networked educational interaction, which play pivotal roles in fostering individual subjectivity development. It is argued that network interaction affords students the opportunity to access a diverse range of conditions for shaping their individual trajectories of linguistic self-education. Moreover, foreign language instruction should encompass not only imparting knowledge and skills for information activities but also cultivating a culture of communication within the digital environment and fostering virtual intercultural competence. In conclusion, harnessing the vast potential of network technologies in foreign language self-learning facilitates language proficiency enhancement and effective development of skills across all types of language activities. Future research should focus on identifying pedagogical conditions conducive to cultivating students’ abilities in creating personalized linguistic self-educational environments